Hydrothermal synthesis of bacterial cellulose–copper oxide nanocomposites and evaluation of their antimicrobial activity. (1st January 2018) - Araújo, Inês M.S.; Silva, Robson R.; Pacheco, Guilherme; Lustri, Wilton R.; Tercjak, Agnieszka; Gutierrez, Junkal; Júnior, José R.S.; Azevedo, Francisco H.C.; Figuêredo, Girlene S.; Vega, Maria L.; Ribeiro, Sidney J.L.; Barud, Hernane S.
Highlights: BC were successfully used for the fabrication of antimicrobial nanocomposites by hydrothermal deposition of Cu derivative nanoparticles. The nanoparticles over BC became more compact and smother for longer heating times and this increase lead to decrease of BC crystallinity. BC-Cu nanocomposites showed antimicrobial activity in vitro against Gram-positive and Gram-negative bacterial species and yeast C. albicans . Abstract: In this work, for the first time bacterial cellulose (BC) hydrogel membranes were used for the fabrication of antimicrobial cellulosic nanocomposites by hydrothermal deposition of Cu derivative nanoparticles (i.e.Cu(0) and CuxOy species). BC-Cu nanocomposites were characterized by FTIR, SEM, AFM, XRD and TGA, to study the effect of hydrothermal processing time on the final physicochemical properties of final products. XRD result show that depending on heating time (3–48 h), different CuxOy phases were achieved. SEM and AFM analyses unveil the presence of the Cu(0) and copper CuxOy nanoparticles over BC fibrils while the surface of 3D network became more compact and smother for longer heating times. Furthermore, the increase of heating time placed deleterious effect on the structure of BC network leading to decrease of BC crystallinity as well as of the on-set degradation temperature. Notwithstanding, BC-Cu nanocomposites showed excellent antimicrobial activity against E. coli, S. aureus and Salmonella bacteria suggesting potential applications as bactericidal films.